D-Zone test for detection of inducible clindamycin resistance using SirScan paper disks and Rosco Neo-Sensitabs at 25 and 15 mm distances - Yusuf, Erlangga; de Bel, Annelies; Bouasse, Jamel; Piérard, Denis (Journal of Medical Microbiology, 2014)
Clindamycin is a possible antibiotic treatment of infections by Gram-positive cocci. However, its use can be limited by inducible clindamycin resistance. To screen for the presence of this type of resistance, the D-zone test is used. The aim of this study was to compare the performance of SirScan paper disks with that of Rosco Neo-Sensitabs for the D-zone test at distances according to dispensers provided by the manufacturers (25 mm) and when the disks are placed at a distance of 15 mm. We studied 364 Gram-stain-positive cocci representing clinical isolates that were resistant to erythromycin and susceptible to clindamycin. Out of these isolates, 207 (57 %) gave a positive D-zone test result at 25 mm distance using SirScan paper disks. When the test was repeated with the same disks placed 15 mm from the 157 (43 %) isolates that had previously given a negative result, 58 (36.9 %) gave a positive D-zone test result. The same isolates were also found to test positive when Rosco Neo-Sensitabs were used. Placing the disks at a distance of 15 mm instead of 25 mm led to an 84.3 % increase in positive D-tests among Staphylococcus aureus, 43.8 % among group B streptococci (GBS) and 6.4 % among coagulase-negative staphylococci (CNS). In conclusion, the SirScan paper disks are equivalent to Rosco Neo-Sensitabs in screening for inducible resistance to clindamycin. The D-test needs to be performed at a shorter distance (15 mm) to prevent false-negative reporting.